Social prescription in the US: A pilot evaluation of Mass Cultural Council's “CultureRx” - Golden, Tasha L.; Maier Lokuta, Alyson; Mohanty, Aanchal; Tiedemann, Alyssa; Ng, T. W. Cherry; Mendu, Maanasa; Morgan, Nicole; Kuge, Maria Nagae; Brinza, Tessa (Frontiers in Public Health, 2023)
Introduction As the field of public health strives to address the impacts of social determinants of health, it has seen increasing interest in community-referral practices that expand health care beyond clinical spaces. However, community arts and culture organizations are rarely included in these practices, despite accumulating evidence of associated health benefits. In addition, such inclusion has not been formally studied. In response, this article offers an evaluation of “CultureRx” in Massachusetts (MA): the first US model of arts on prescription. The program is a partnership between 20 healthcare providers and 12 cultural organizations, in which providers can offer “prescriptions” to cultural experiences to support patients' health. Methods Evaluation was undertaken to illuminate participant experiences, program successes and barriers, and recommendations for further development. The cultural organizations collected participant data (n = 84) and completed surveys about their own experiences (n = 12). Authors conducted semi-structured focus groups and interviews with healthcare providers (n = 33). Data analysis was customized for each dataset. Results Findings indicate that participants enjoyed and hoped to repeat their prescribed experiences, which they saw as beneficial to wellbeing. Providers identified the program as a new and critical addition to their toolkits; they also indicated it had a positive effect on their own wellbeing. Cultural organizations reported varied challenges, learnings, and recommendations. Conclusion The CultureRx pilot suggests that integrating arts/culture assets into health and social care approaches can enrich and improve traditional US models of community referral. By including arts/culture resources when addressing social determinants of health, communities will be better positioned to equitably and holistically advance health.